Implementasi Metode Linear Addition untuk Perancangan Efek Mask Lightning - Kristoko Dwi Hartomo (Faculty of Industrial Technology Universitas Islam Indonesia, 2005)
Digital picture development is picture processing using digital computer in order to get different picture or another picture which suits with the needs. One example of picture development is mask lighting effect with linear addition method. The main principle of linear addition method is by adding intensity to every pixel colour by adding every pixel with a variable. This paper focuses on the implementation of linear addition method to give lighting effect on picture. Keywords : mask lighting, linear addition, pixel.